2019
DOI: 10.1021/acs.jpcc.9b01320
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subphase pH and Temperature on the Aggregation Behavior of Poly(lauryl acrylate)-block-poly(N-isopropylacrylamide) at the Air/Water Interface

Abstract: Effects of subphase pH and temperature on the aggregation behavior of a thermosensitive amphiphilic diblock copolymer poly­(lauryl acrylate)-block-poly­(N-isopropylacrylamide) (PLA-b-PNIPAM) at the air/water interface and the morphologies of its Langmuir–Blodgett (LB) films were characterized with the Langmuir film balance technique and atomic force microscopy, respectively. The surface pressure–molecular area isotherms shift positively with the increase of subphase pH, and there exist two quasi-plateaus under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(48 citation statements)
references
References 44 publications
2
44
2
Order By: Relevance
“…When the temperature is higher than the LCST of PNIPAM, the core–shell structures are destroyed and the drug is released . More recently, we found that amphiphilic diblock copolymer poly­(lauryl acrylate)- block -poly­( N -isopropylacrylamide) (PLA- b -PNIPAM) exhibited the LCST behavior at the air/water interface under neutral and alkaline subphase conditions, which is consistent with that of PNIPAM-containing copolymers in aqueous solutions. Furthermore, it has been found that salt ions, particularly anions, have significant effects on the LCST of PNIPAM aqueous solutions related to the famous Hofmeister series. The typical order of the anion series is as follows: CO 3 2– > SO 4 2– > S 2 O 3 2– > H 2 PO 4 – > F – > Cl – > Br – ≈ NO 3 – > I – > ClO 4 – > SCN – .…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…When the temperature is higher than the LCST of PNIPAM, the core–shell structures are destroyed and the drug is released . More recently, we found that amphiphilic diblock copolymer poly­(lauryl acrylate)- block -poly­( N -isopropylacrylamide) (PLA- b -PNIPAM) exhibited the LCST behavior at the air/water interface under neutral and alkaline subphase conditions, which is consistent with that of PNIPAM-containing copolymers in aqueous solutions. Furthermore, it has been found that salt ions, particularly anions, have significant effects on the LCST of PNIPAM aqueous solutions related to the famous Hofmeister series. The typical order of the anion series is as follows: CO 3 2– > SO 4 2– > S 2 O 3 2– > H 2 PO 4 – > F – > Cl – > Br – ≈ NO 3 – > I – > ClO 4 – > SCN – .…”
Section: Introductionsupporting
confidence: 79%
“…The weight-average molecular weights of PLA and PNIPAM blocks in the copolymer PLA- b -PNIPAM were 6000 and 12 000, respectively . HPLC-grade chloroform was used to prepare the spreading solution of PLA- b -PNIPAM (0.50 mg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…32 At low ionic strength (0.15 mol/L), the A 0 values of PDMAEMA18%-PLMA appear at large mmA (>15 nm 2 ). This is because the strongly hydrated anions (Cl − and SO 4 2− ) can polarize the water molecules 34 surrounding the short protonated PDMAEMA blocks and thus destroy their hydrogen bonds, resulting in the adsorption of the latter to the interface. Upon compression, an obvious plateau appears at 12 mN/m corresponding to the PDMAEMA submergence in water, which is similar to that appearing under alkaline conditions without salts.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…After a 20 min period for the full evaporation of THF, each initial surface pressure was below 0.20 mN/m. Finally, the monolayer was compressed by the symmetrical movement of two barriers (5 mm/min), and each isotherm was obtained with two almost overlapped curves . During the hysteresis measurement, the Langmuir monolayer was compressed to mm A of 5 nm 2 and maintained for 30 s, and then the barriers moved to the start positions.…”
Section: Methodsmentioning
confidence: 99%
“…However, their isotherms at 40 C significantly move to the right with the A 0 values of 16.1 and 16.2 nm 2 , respectively. This is because high temperature increases the mobility of the cationic blocks 35 whose electrostatic repulsion makes them more stretched. At 40 C, the collapse pressure of qPDMAEMA87%-PLMA (40 mN/m) is higher than that of qPDMAEMA30%-PLMA (15 mN/m) because the stronger underwater electrostatic repulsion between the longer qPDMAEMA chains delays the monolayer collapse.…”
Section: Subphase Temperature Effect On the Isothermsmentioning
confidence: 99%